ANALYSIS OF MANGROVE HEALTH USINGHEMISPHERICAL PHOTOGRAPHY METHOD IN COASTAL CENTER TAPANULI REGENCY, NORTH SUMATERA PROVINCE - Muhammad Isnan Alindra; Joko Samiaji; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             Hemispherical photography method is one of the new methods used and developed in Indonesia in determining mangrove status. The research was conducted in February-March 2019 in coastal Central Tapanuli Regency, North Sumatra  Province.The purpose of this research was to analyze the status of the health conditions of the mangrove community by knowing the value of density, percentage of cover and important value index based on the categories specified in the Decree of the Minister of Environment No. 201 of 2004 about Standard Criteria and Guidelines for Determining Mangrove Damage.The results of the research showed that environmental ecological conditions supported the existence of mangroves.Morphological identification was obtained as many as 8 species from 3 familiesof mangroves. Based on the standard criteria for mangrove damage (Decree of the Minister of Environment No. 201 of 2004), the percentage of mangrove cover was included in the criteria of being medium to heavy with a value 72,61%-75,64%. The density of mangroves is in the medium to dense category with a range between 1400-1511 trees / ha. The overall condition of the mangrove forest was considered as good and healthy. The analysis of Important Value Index (INP) of each type of mangrove was found in the range of values between 3,25%-100,77%, with the highest index of important species was found in Rhizophora apiculata with a value of 100.77% and the lowest was in Scyphiphora hydrophyllacea with a value of 3,25%. Keywords:Central Tapanuli Regency, Mangrove, hemispherical photography, Percentage cover,Density